2013
DOI: 10.1073/pnas.1220018110
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila seminal protein ovulin mediates ovulation through female octopamine neuronal signaling

Abstract: Across animal taxa, seminal proteins are important regulators of female reproductive physiology and behavior. However, little is understood about the physiological or molecular mechanisms by which seminal proteins effect these changes. To investigate this topic, we studied the increase in Drosophila melanogaster ovulation behavior induced by mating. Ovulation requires octopamine (OA) signaling from the central nervous system to coordinate an egg's release from the ovary and its passage into the oviduct. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
155
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 68 publications
5
155
0
Order By: Relevance
“…OA binds to its receptor Octopamine receptor in mushroom body (Oamb) in mature follicle cells to induce an intracellular calcium rise, Mmp2 activation, and follicle rupture (12). Drosophila ovulation is also regulated by multiple ovarian extrinsic factors, including secretions from the oviduct (13), female reproductive glands (14), and male accessory glands (15,16). However, a role for steroid signaling in Drosophila ovulation has never been established.…”
mentioning
confidence: 99%
“…OA binds to its receptor Octopamine receptor in mushroom body (Oamb) in mature follicle cells to induce an intracellular calcium rise, Mmp2 activation, and follicle rupture (12). Drosophila ovulation is also regulated by multiple ovarian extrinsic factors, including secretions from the oviduct (13), female reproductive glands (14), and male accessory glands (15,16). However, a role for steroid signaling in Drosophila ovulation has never been established.…”
mentioning
confidence: 99%
“…35 Since artificially increasing OA neuronal signaling compensated for lack of ovulin receipt during mating, this result suggested that ovulin increases ovulation rates by stimulating the OA pathway.…”
Section: Reproductive Hackingmentioning
confidence: 99%
“…37 Consistent with this view of OA action, measures of oviduct sarcomere length showed that oviduct muscles do relax after mating. This postmating muscle relaxation depends on the female's OA signaling 35 : only females that could produce OA responded to mating by relaxing their oviduct muscles. Further, artificially and selectively increasing the activity of OA neurons using the thermally activated TrpA channel 38,39 was also able to induce the relaxation in oviduct muscles.…”
Section: Reproductive Hackingmentioning
confidence: 99%
See 2 more Smart Citations